A COVID-19 Silver Lining-Decline in Antibiotic Resistance in Ischemic Leg Ulcers during the Pandemic: A 6-Year Retrospective Study from a Regional Tertiary Hospital (2017-2022) - Amaraporn Rerkasem; Pak Thaichana; Nuttida Bunsermvicha; Rawee Nopparatkailas; Supapong Arwon; Saranat Orrapin; Termpong Reanpang; Poon Apichartpiyakul; Saritphat Orrapin; Boonying Siribumrungwong; Nongkran Lumjuan; Kittipan Rerkasem; et al. (MDPI AG, 2023)
Antibiotic resistance (AR) associated with chronic limb-threatening ischemia (CLTI) poses additional challenges for the management of ischemic leg ulcers, increasing the likelihood of severe outcomes. This study assessed AR prevalence in bacteria isolated from CLTI-associated leg ulcers before (1 January 2017-10 March 2020; n = 69) and during (11 March 2020-31 December 2022; n = 59) the COVID-19 pandemic from patients admitted with positive wound cultures to a regional hospital in Chiang Mai (Thailand). There was a marked reduction in AR rates from 78% pre-pandemic to 42% during the pandemic (p < 0.0001), with rates of polymicrobial infections 22 percentage points lower (from 61% to 39%, respectively; p = 0.014). There were reduced AR rates to amoxicillin/clavulanate (from 42% to 4%; p < 0.0001) and ampicillin (from 16% to 2%; p = 0.017), as well as multidrug resistance (19% to 8%; p = 0.026). Factors associated with increased AR odds were polymicrobial infections (adjusted odds ratio (aOR) 5.6 (95% CI 2.1, 15.0); p = 0.001), gram-negative bacteria (aOR 7.0 (95% CI 2.4, 20.5); p < 0.001), and prior use of antibiotics (aOR 11.9 (95% CI 1.1, 128.2); p = 0.041). Improvements in infection control measures and hygiene practices in the community during the pandemic were likely key factors contributing to lower AR rates. Thus, strategic public health interventions, including community education on hygiene and the informed use of antibiotics, may be crucial in mitigating the challenges posed by AR in CLTI. Further, advocating for more judicious use of empirical antibiotics in clinical settings can balance effective treatment against AR development, thereby improving patient outcomes.